Voltammetric study on the electrodeposition of aspirin on a vitreous carbon electrode - Corona Castro, Jair Azael; Mendoza Huizar, Luis Humberto (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2014)
Aspirin is one of the most widely used medications in the world due to its analgesic effect. When it is consumed by human beings, the latter is unable to fully metabolize it and part of it is discarded by physiological mechanisms and incorporated into drainage water. Because of this, aspirin has recently been considered an emerging water contaminant. This has led to an extensive search for degradation methods that allow their mineralization in wastewater to re-incorporate them into human activities. Given the above, in the present work it is proposed to use electrodeposition as a means to remedy water contaminated with this drug. A voltammetric study was carried out from a solution containing 0.001M aspirin and 0.2M ZnCl2 as support electrolyte, on a vitreous carbon electrode, with an Ag/AgCl electrode as reference and a graphite electrode as auxiliary. The experiments were carried out with the help of an EPSILON potentiostat-galvanostat. The results obtained so far indicate that it is possible to electrodeposit aspirin from chloride-based baths and on a vitreous carbon electrode. In the voltammograms obtained, it is possible to observe during the direct sweep in the cathodic direction the formation of a reduction peak at -1.14V (A). In the reverse scan, the formation of other peaks (B and C) at -1.29V and -1.24V and an electrochemical signal (D) at 0.24V, corresponding to electrodeposited aspirin, are noted. Plot of peak current against square root of scan rate indicates linear behavior, suggesting diffusion control.